Intestinal spirochetosis - Nadal,Luis Roberto Manzione (2011)
The intestinal spirochetosis (IS) is a histologically defined by the presence of spirochetal microorganisms connected to the apical cell membrane of the colorectal epithelium. The disease is caused by a heterogeneous group of bacteria. In humans, Brachyspira aalborgi and Brachyspira pilosicoli are prevalent. The incidence ranges from 1% in developed countries to 34% in poorer areas. It affects 62.5% of colonized areas, as well as men who have intercourse with men (MSM) and those with the human immunodeficiency virus (HIV) infected. Clinical significance of such colonization is still not clear. Most infected people are asymptomatic. At the presence of gastrointestinal symptoms, treatment with metronidazole is effective. Due to unknown reasons, MSM and HIV-positive men are more likely to be symptomatic. Treponema pallidum infection must be excluded, since this agent may cause serious and permanent complications, and because the treatment is different.